The wild Christmas reindeer - Brett, Jan, 1949- (New York : Putnam, 1990)
After a few false starts, Teeka discovers the best way to get Santa$1 (Bs reindeer ready for Christmas Eve.s
Keywords: Reindeer -- Fiction; Christmas -- Fiction